TANGGUNG JAWAB NEGARA ATAS DIGUNAKANNYA SENJATA SPACE-BASED MISSILE INTERCEPTOR SEBAGAI BENTUK UPAYA SELF-DEFENSE DARI NEGARA PENYERANG TERHADAP NEGARA PIHAK KETIGA DITINJAU DARI HUKUM INTERNASIONAL - Virajati Adhazar; Suhaidi Suhaidi; Sutiarnoto Sutiarnoto; Jelly Leviza (Fakultas Hukum Universitas Komputer Indonesia, 2022)
Self-defense as an inherent right owned by a country is regulated in Article 51 of the UN Charter and due to the use of Space-Based Missile Interceptor (SBMI) weapons in space, the 1967 outer space treaty must also be guided. Because Article 4 of the 1967 Outer Space Treaty prohibits the use of weapons in space, the legality of using SBMI weapons is questionable. Therefore, this study was conducted to determine the legal provisions, forms of state accountability and the process of prosecuting compensation for countries using these weapons according to international law. The results of the study indicate that the use of SBMI weapons does not conflict with international law, because it is based on Article 103 of the UN Charter which states that if there are provisions in other legal rules that are contrary to the UN Charter, the UN Charter must be guided. So that self-defense actions based on Article 51 of the UN Charter do not violate the law. The party that must be absolutely responsible is the country that started the conflict, because it has violated the rules of international law in Article 2 paragraph (4) of the UN Charter and international humanitarian law. The compensation process is carried out according to the rules of the space liability convention 1972 and if in practice the party who is responsible does not show good faith in providing compensation, then it can be continued by referring to the dispute resolution process in the UN Charter.